Dampak Efisiensi Pengelolaan Anggaran Terhadap Kinerja Organisasi: Bukti dari Rumah Sakit Badan Layanan Umum TNI AL di Indonesia - Santo Wirawan Harefa; Amimul Ummah Bay; Mohamad Rachmad (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the impact of budget management efficiency on organizational performance in a military Public Service Agency (BLU) hospital, with a case study at RSPAL dr. Ramelan Surabaya. As a BLU institution, the hospital possesses budgetary flexibility that allows for the optimization of direct spending and improvement in service quality. A descriptive quantitative approach was employed, with data collected through documentation, questionnaires, and semi-structured interviews. The results show that budget efficiency—reflected in improved budget realization ratios, strategic expenditure allocation, and the implementation of integrated financial information systems—has a positive and significant effect on organizational performance. Performance indicators such as BOR (Bed Occupancy Rate), ALOS (Average Length of Stay), and non-tax revenue (PNBP) improved alongside budget efficiency. These findings affirm that efficiency is not merely a fiscal control tool but a strategic mechanism to enhance service performance in military hospitals.